MENGHAPUS STIGMA KESEHATAN MENTAL DI INDONESIA MELALUI PENDEKATAN SILA KEMANUSIAN YANG ADIL DAN BERADAB - Kadek Anik Yulia Dewi; Nur Aida Kholis; Afwa Isnainiyah; Nabilla Aurellia Pramesti; Khusnul Khotimah (JURNAL ILMIAH NUSANTARA, 2026)
Mental health stigma is a major barrier to help-seeking and recovery among individuals with mental disorders. It generates prejudice, discrimination, and structural obstacles that affect quality of life and access to mental health services. This article aims to systematically analyze the scientific literature on mental health stigma in society, including its definitions, types, causes, impacts, cross-cultural manifestations, and the interventions that have been implemented. A Systematic literature review (SLR) was conducted by searching major academic databases such as Google Scholar using keywords related to stigma and mental health, public attitudes, and discrimination. Approximately 200 unique articles were identified, evaluated, and analyzed thematically. Mental health stigma commonly appears in the form of stereotypes, prejudice, and discriminatory actions toward individuals experiencing mental disorders. On the other hand, improving mental health literacy through psychoeducation, awareness campaigns, and educational programs in schools and communities is an important strategy to reduce stigma. When linked to the values of Pancasila, particularly the second principle, “Just and Civilized Humanity,” these efforts reflect respect for human dignity and the provision of fair and non-discriminatory treatment.